TIKTOK SEBAGAI MEDIA PEMBELAJARAN MEMPENGARUHI PENINGKATAN KECINTAAN AKAN MAKANAN TRADISIONALTIKTOK SEBAGAI MEDIA PEMBELAJARAN MEMPENGARUHI PENINGKATAN KECINTAAN AKAN MAKANAN TRADISIONAL - Adinda Jihan Nur Rahmah; Ayu Mawariz; 21dzikri_millati21; Melawati Sawitri; Ratna Fitria; Supriyono Supriyono (Jurnal Global Citizen : Jurnal Ilmiah Kajian Pendidikan Kewarganegaraan, 2026)
In this modern era, it is very easy to access information media with today's technological sophistication. Tiktok is one of the information media that is easily accessible to all groups with different goals. Tiktok can affect changes in a person's behavior which has a huge impact on the private individual from using this TikTok application. The purpose of this study is to determine the effect of Tiktok social media on high school and vocational students as an increase in love for the homeland through traditional food displayed in videos in Tiktok. The research method used in this article is quantitative method. The type of research conducted is associative research. Associative research aims to determine the influence between two variables. The research variable aims to determine the influence of social media. From the results of the research conducted, it can be seen that SMK students know more about traditional klepon food with a final percentage of 70%. In the second study we found out that SMK students wanted to make traditional klepon food after watching the video presented with a percentage of 53.3. Whereas in the third study SMA had the most values stating that traditional klepon food was very interesting with a total percentage of 60%. Then in the fourth study, SMK had the highest score stating that the tiktok video presented made students want to buy traditional klepon food with a final percentage of 60%. Meanwhile, in the fifth and sixth studies, there was a quite far comparison where high schools felt very proud of traditional klepon food and felt that klepon should be a typical Indonesian food with a percentage of 90% and 96.7%. The results of the calculation using the Likert scale are included in the criteria strongly agree with the calculation results contained in 80-100%. Keywords: TikTok; Traditional Food; Learning Media